2016
DOI: 10.1002/ange.201610168
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Oxidative C−C and N−N Coupling of Diarylamines and Synthesis of Spiroacridines

Abstract: We describe iron-catalyzed intermolecular oxidative coupling reactions of diarylamines to form substituted 2,2'bis(arylamino)biaryl compounds, tetraarylhydrazines, and 5,6dihydrobenzo[c]cinnolines with the same hexadecafluorinated iron-phthalocyanine catalyst. The mild formation of CÀC or N À N bonds was controlled by the use of acidic or basic additives. In contrast to most iron-catalyzed dehydrogenative coupling reactions, ambient air could be used as the sole oxidant. Moreover, iron(III) chloride hexahydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…[a] Reaction conditions: A: 3 (1.0 equiv), FePcF 16 (2×0.5 mol%), MsOH (10 mol%), CH 2 Cl 2 , rt, air; B: 3 (1.0 equiv), FePcF 16 (2×2.5 mol%), MsOH (50 mol%), CH 2 Cl 2 , rt, air; C: 3 (1.0 equiv), FePcF 16 (1×1.0 mol%), MsOH (10 mol%), CH 2 Cl 2 , rt, air (1×5.0 mol% FePcF 16 and 50 mol% MsOH for 3 e ); [34a] D: 3 (1.0 equiv), O(FeTPPF 28 ) 2 (1×1.5 mol%), BF 3 ⋅OEt 2 (20 mol%), CH 2 Cl 2 , rt, air; [34c] yields refer to isolated products. [b] Using reaction conditions B, cleavage of the acetal occurred.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[a] Reaction conditions: A: 3 (1.0 equiv), FePcF 16 (2×0.5 mol%), MsOH (10 mol%), CH 2 Cl 2 , rt, air; B: 3 (1.0 equiv), FePcF 16 (2×2.5 mol%), MsOH (50 mol%), CH 2 Cl 2 , rt, air; C: 3 (1.0 equiv), FePcF 16 (1×1.0 mol%), MsOH (10 mol%), CH 2 Cl 2 , rt, air (1×5.0 mol% FePcF 16 and 50 mol% MsOH for 3 e ); [34a] D: 3 (1.0 equiv), O(FeTPPF 28 ) 2 (1×1.5 mol%), BF 3 ⋅OEt 2 (20 mol%), CH 2 Cl 2 , rt, air; [34c] yields refer to isolated products. [b] Using reaction conditions B, cleavage of the acetal occurred.…”
Section: Resultsmentioning
confidence: 99%
“…We have an ongoing project directed towards the application of iron compounds as catalysts for convenient oxidative transformations, since iron compounds represent environmentally benign catalysts [30,31] . In this context, we found that the hexadecafluorophthalocyanine–iron(II) complex FePcF 16 , [32,33] which under air is immediately oxidized to μ‐oxo‐bis[(hexadecafluorophthalocyanine)iron(III)] (O[FePcF 16 ] 2 ) (Figure 2), [33f] shows exceptional reactivity as catalyst for the oxidative C−C homocoupling reaction of diarylamines 3 to 2,2′‐bis(arylamino)‐1,1′‐biaryl compounds 4 [34a,b] . The iron‐catalyzed oxidative coupling of the diarylamines 3 a – l using hexadecafluorophthalocyanine–iron(II) (FePcF 16 ) as catalyst and methanesulfonic acid as additive under aerobic conditions [34a] provided the compounds 4 a – l in short reaction times and 51–77 % yield (Table 1; see also: Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these transformations, air or molecular oxygen are ideal oxidants because they are abundant, cheap, and generates at best only water as the by‐product. In recent years, iron‐catalyzed aerobic oxidative reactions through C−H functionalization have received considerable attention owing to their efficiencies, low cost, and environmentally friendly features, and have become a powerful tool for the construction of synthetically valuable heterocycles, such as indolizines, isoxazoles, imidazoles, spiroacridines, quinazolines, 1,3‐benzazoles, and pyridines . Our interest in aerobic oxidation reactions,, prompted us to study iron‐catalyzed oxidative annulation reactions that could employ air (O 2 ) as an oxidant, and we describe here a straightforward method for the construction of 3,4‐dihydro‐2 H ‐1,2,4‐benzothiadiazine 1,1‐dioxides and quinazolines via iron‐catalyzed oxidative condensation of benzylamines with 2‐aminobenzenesulfonamide/2‐aminobenzylamines (Scheme , eq.…”
Section: Introductionmentioning
confidence: 99%